Characterisation of Outer Himalayan Watersheds and Management Strategies for Moderated and Sustained Stream Flow Regimes - Sastry, G.; Sharma, S. K. (Indian Forester, 2001)
The Himalayas cover an area of about 50 million ha and there has been a very rapid increase in the developmental activities. A near exponential population growth has placed a further heavy demand on already limited natural resources. Debris load production from steam banks, land slides and mine waste causes in-equilibrium in stream flow regimes and further cause extensive damage to life and property in the valley lands. The paper deals with - (a) determination of Himalayan Watershed Characteristics and assessment of relative erosion proneness and torrent formation, (b) to establish relationships between channel morphological parameters with drainage area and channel length upstream, and (c) to evaluate the performance of the management strategies in the reduction of runoff and debris load production rates. The studies conducted clearly indicate that - (a) bed material size increased up to about one-fourth to onethird of the length of torrent and decreased, thereafter, which is attributed to both colluvial and gravitational forces. (b) an inverse relationship exist between channel width and local bed slope, (c) the reclamation measures reduce runoff from almost 55 per cent to 33 per cent and debris load from near 550 tonnes/ha/year to 8.0 tonnes/ha/yr. When conservation measures are implemented scientifically then it would not only reduce runoff and debris load but also improve dry weather flow and sustain for a longer period i.e., from 100 days to 240 days.